Density-conditional forecasts in dynamic multivariate models - Michael K. Andersson; Stefan Palmqvist; Daniel F. Waggoner (Sveriges Riksbank, 2010)
When generating conditional forecasts in dynamic models it is common to impose the conditions as restrictions on future structural shocks. However, these conditional forecasts often ignore that there may be uncertainty about the future development of the restricted variables. Our paper therefore proposes a generalization such that the conditions can be given as the full distribution of the restricted variables. We demonstrate, in two empirical applications, that ignoring the uncertainty about the conditions implies that the distributions of the unrestricted variables are too narrow.
Keywords: C53; E37; E52; 330; Central Bank; Market Expectation; Restrictions; Uncertainty